Combined Thoracic Endovascular Aortic Repair and Neurosurgical Intervention for Injury Due to Posterior Spine Surgery - Carmignani, Amedeo; Lentini, Salvatore; Acri, Edvige; Vazzana, Giovanni; Campello, Mauro; Volpe, Pietro; Acri, Ignazio E.; Spinelli, Francesco (Journal of cardiac surgery, 2013)
Aortic injuries represent a rare but life‐threatening complication of spinal surgery. Perforation of the aorta due to pedicle screw penetration or misplacement can lead to immediate bleeding with hemodynamic instability or to pseudoaneurysm development with delayed risk of rupture, which can occur weeks to months later. Recently, thoracic endovascular aortic repair (TEVAR) in aortic trauma has contributed to a reduction of both mortality and morbidity. The literature on this subject is reviewed. doi: 10.1111/jocs.12052 (J Card Surg 2013;28:163–167)